2020
DOI: 10.1016/j.xhgg.2020.100008
|View full text |Cite
|
Sign up to set email alerts
|

Deep whole-genome sequencing of multiple proband tissues and parental blood reveals the complex genetic etiology of congenital diaphragmatic hernias

Abstract: Summary The diaphragm is critical for respiration and separation of the thoracic and abdominal cavities, and defects in diaphragm development are the cause of congenital diaphragmatic hernias (CDH), a common and often lethal birth defect. The genetic etiology of CDH is complex. Single-nucleotide variants (SNVs), insertions/deletions (indels), and structural variants (SVs) in more than 150 genes have been associated with CDH, although few genes are recurrently mutated in multiple individuals and muta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 127 publications
1
4
0
Order By: Relevance
“…A significant challenge in the diagnosis and treatment of CDH has been low yields of genetic testing, with a pathogenic genetic change identified in only 30% of cases (Yu et al, 2020). Our results further support recent studies that employ WGS which found a diverse array of mutational types that cause CDH (SNV/INDELs, SVs, and splice site changes) and show the utility of WGS as a first‐line diagnostic tool (Bogenschutz et al, 2020; Sweeney et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…A significant challenge in the diagnosis and treatment of CDH has been low yields of genetic testing, with a pathogenic genetic change identified in only 30% of cases (Yu et al, 2020). Our results further support recent studies that employ WGS which found a diverse array of mutational types that cause CDH (SNV/INDELs, SVs, and splice site changes) and show the utility of WGS as a first‐line diagnostic tool (Bogenschutz et al, 2020; Sweeney et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Typically, each gene or copy-number variant (CNV) associated with CDH accounts for at most 1%-2% of affected individuals. 9 The full spectrum of genomic variants has been associated with CDH, including chromosome aneuploidies (10%), copy-number variants (CNVs) (3%-10%), monogenic conditions (10%-22%), and emerging evidence for oligogenic causes 1 (CNVs and individual genes 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Congenital diaphragmatic hernia (CDH) is a malformation in which the diaphragm fails to properly form, resulting in the abdominal viscera invasion into the thoracic cavity during embryonic development ( Sefton et al, 2018 ). Despite the moderate incidence (1:3,000 new-born), the etiology of the disease is not completely understood due to the heterogeneous and multifactorial players ( Bogenschutz et al, 2020 ). Indeed, high proportion of CDH cases may be due to new dominant mutations, but epigenetic events could also be a causal factor ( Pober et al, 2005 ).…”
Section: Muscle Diseases and Myopathiesmentioning
confidence: 99%